Anodização processada por corrente contínua e pulsada de uma liga al-si 6,75% tratada termicamente - Regone, Natal Nerímio [UNESP]; Freire, Célia Marina Alvarenga; Ballester, Margarita (My University, 2010)
The purpose of this work was to find a heat treatment process to Al-6.75% Si alloy that makes the dispersion of Si element in order to overcome the difficulties in the anodizing process. Samples were put in an oven at 540°C during 12 hours, and afterwards immersed in boiling water. After heat treatment, the thermally formed oxide was removed with sandpaper. The alloys were anodized during 30 minutes using pulsed and direct current in H2SO 4(6% volume) and H2C2O4 (5% weight) solution at 22°C. The film thickness and uniformity of anodic oxide film were observed in cross section by optical microscopy. Without heat treatment of the Al-Si alloy, the anodic film formed by direct or pulsed current has non-uniform thickness. It was found that heat treatment leads to dispersion of silicon particles in Al matrix. And that the formed anodic film is more uniform film. The film uniformity is even better when pulsed current is used. Copyright © (2010) by Associação Brasileira de Metalurgia Materiais e Mineração (ABM).
Anodizing processed by direct and pulsed current of al-si alloy 6.5% heat treated
Keywords: Al-Si alloys; Anodizing; Heat treatment